Lessons learned from conducting six multi-country mixed-methods effectiveness research studies on water, sanitation, and hygiene (WASH) interventions in humanitarian response. - Lantagne, Daniele.; Lehmann, Lilian.; Yates, Travis.; Gallandat, Karin.; Sikder, Mustafa.; Domini, Marta.; String, Gabrielle. (Tufts University. Tisch Library., 2021)
Keywords: Effectiveness research, Ethics, Humanitarian response, Operational research, Water, sanitation and hygiene.; Springer Open.